An Evaluation of Public School District Tobacco Policies in St. Louis County, Missouri. (8th July 2013) - Barbero, Colleen; Moreland‐Russell, Sarah; Bach, Laura E.; Cyr, Julianne
ABSTRACT: BACKGROUND: One way to address tobacco use by youth is for primary and secondary schools to adopt and implement comprehensive tobacco policies. The purpose of this study was to evaluate the comprehensiveness of tobacco policies in St. Louis County, Missouri public school districts. METHODS: We evaluated the strength of tobacco policies from all 23 public school districts located in the county using the Center for Tobacco Policy Research's School Tobacco Policy Index, a standardized tool for rating school tobacco policies. RESULTS: The districts averaged a score of 24.4 of 40 possible points on the Index. Policies scored highest on the Tobacco‐Free Environment domain and lowest on the Enforcement domain. Policies averaged about half of the total possible points for the Prevention and Treatment Services and Policy Organization domains. CONCLUSION: Despite more than a decade of efforts by the Centers for Disease Control and Prevention to improve school tobacco policies, this study shows that policies in St. Louis County districts have yet to meet the standard of comprehensiveness. It is recommended that schools adopt policies that are comprehensive and that address all domains of the School Tobacco Policy Index.